Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Rafi Dima Putra; Rilla Gantino (Faculty of Economic and Business, 2021)
Business competition encourages companies to continue to improve their performance in order to increase company value. This study aims to determine the effect of profitability, leverage, and company size on firm value. The data analysis method used is multiple linear regression analysis. The test results show that profitability, leverage, and company size simultaneously affect firm value in the pharmaceutical sector and in the property & real estate sector. Profitability has no effect on firm value in the pharmaceutical sector and profitability has an effect on firm value in the property & real estate sector. Leverage affects company value in the pharmaceutical sector and property & real estate companies. Firm size has no effect on firm value in both sectors. Through the results of this study, companies in the property and real estate sector should strive to continue to increase profitability and leverage so that company value increases, meanwhile, company value in the pharmaceutical sector will increase, influenced by leverage.Cara Mengutip:Putra, R. D., & Gantino, R. (2021). Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Nilai Perusahaan. Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.20338.